Pengaruh Media Audio Visual Terhadap Perkembangan Kognitif Anak Usia Dini - Azizah Trisnani; Devi Agustiana; Deka Meuthia Novari (Program Studi Pendidikan Islam Anak Usia Dini, 2026)
Cognitive ability is an important aspect of early childhood education that can be developed through the use of engaging learning media tailored to children's characteristics. This study aimed to analyze the effect of audiovisual media on the cognitive development of early childhood learners in the universe theme, particularly the topic of rainbows. The research employed a quantitative approach using a simple experimental design conducted at TK Harapan Setia Negara. The participants consisted of 13 children aged 5–6 years from Group B3. The study was carried out in two stages, involving two learning treatments: instruction without audiovisual media and instruction using audiovisual media. Data were collected through observation using a developmental checklist that assessed children's ability to recognize and name the colors of the rainbow, arrange rainbow colors in sequence, demonstrate curiosity, participate in simple experimental activities, and create rainbow-shaped folding crafts. The findings revealed that all developmental indicators improved after the implementation of audiovisual media in learning activities. Prior to the treatment, most children were categorized as Not Yet Developed (NYD) and Beginning to Develop (BD). After the treatment, the majority of children reached the categories of Developed as Expected (DE) and Very Well Developed (VWD). These results indicate that audiovisual media are effective in supporting the cognitive development of early childhood learners. This study contributes to the advancement of science and technology by providing empirical evidence that audiovisual media can serve as an innovative learning tool to enhance both the quality of the learning process and learning outcomes in early childhood education.